PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS KEMBALI DONGENG SISWA KELAS VII SMP NEGERI 22 PADANG - Nursaid, Wiwi Eka Putri, Abdurrahman, (Universitas Negeri Padang, 2017)
The purpose of this study is (1) to determine the level of skills to re-writing fairy tales of students VII SMP Negeri 22 Padang without using problem based learning aided media images. (2) to find out the skill level of re-writing the students of the country VII class SMP Negeri 22 Padang by using assisted problem based learning aided images series. (3)analyze the effect of applications of problem based learning model of media assisted drawing writing skills li tale students VII SMP Negeri 22 Padang. This type of research is quantitative with quasi-experiment methode. The use of problem based learning model aided media images berrei affect the skills to re-writing tales students VII SMP Negeri 22 Padang.Â Kata kunci: pengaruh, model problem based learning berbantuan media gambar berseri, menulis kembali dongeng.